Eksplorasi Etnomatematika Pada Benteng “Van Den Bosch” Ngawi - Susanto, Doni; Untari, Erny; Khoiri, Halwa Annisa (Polinomial : Jurnal Pendidikan Matematika, 2026)
Mathematics is often regarded as a discipline detached from social and cultural contexts, even though the development of mathematical concepts is inherently connected to human experiences in understanding space, form, and everyday needs. Ethnomathematics emerges as a perspective that highlights this interrelationship by positioning mathematical practices as an integral part of culture. This study aims to examine the application of mathematical concepts found in Van den Bosch Fort in Ngawi, a nineteenth-century colonial structure built by the Dutch for defense purposes and for monitoring strategic routes at the confluence of the Bengawan Solo and Madiun rivers. Employing a qualitative approach with an ethnographic method, this research conducted direct observations of the building’s structure, interviews with local informants, and visual documentation to identify mathematical elements embedded within the fort’s architectural features. The data analysis techniques used were data collection, data presentation and drawing conclusions. The findings reveal that various concepts of plane and solid geometry are represented through the shapes of the gateways, doors, windows, guard posts, and supporting pillars, which include squares, rectangles, equilateral triangles, right triangles, semicircles, and cylinders. These results demonstrate that colonial architecture was not solely designed based on strategic or military considerations, but also incorporated systematic mathematical principles. In addition to providing theoretical contributions to ethnomathematics studies, this research holds practical implications for the development of culture-based mathematics learning. By utilizing historical buildings as learning resources, students are expected to gain a more contextual and meaningful understanding of mathematics while cultivating an appreciation for the historical and local values embodied in Van den Bosch Fort.